Effect of Pulsed Currents on the Springback Reduction of Ultra-High Strength Steels. (2017) - Song, Junghan; Jang, Injea; Gwak, Suhyun; Noh, Wooram; Lee, Jongsup; Bae, Gihyun; Kim, Daeyong
Abstract: In this paper, the effect of a single pulsed electric current on the springback reduction of UHSS is investigated by experiments. To do this, a current pulse generator and a bending setup were designed and manufactured. V-bending tests of the 1180 grade steel sheet under a pulsed electric current were then carried out for evaluating springback reduction. The electric pulse was applied to the specimen with constant amplitude of electric current and duration time after the specimen was deformed. The influence of the two adjustable electrical parameters pulse duration and current density on springback was analyzed. The experimental results showed that springback angles are sharply decreased with increasing current densities and pulse durations.